The expression "p + 2q" represents the sum of a variable p and twice the value of another variable q. This can also be written as p + 2 * q, where the asterisk denotes multiplication. In algebraic terms, this expression cannot be simplified further unless specific values are assigned to the variables p and q.
Chat with our AI personalities
The difference of p and q can be written : p - q Twice the difference is therefore 2 x (p - q) which can also be written as 2(p - q) OR 2p - 2q. Consequently you can create another variable (say) y and make this equal to twice the difference of p and q by simply writing, y = 2(p -q)
2p+4q=16 (now divide the equation by two) p+2q=8 (now subtract 2q) p=8-2q 7p+12q=52 (substitue the answer you got for p in the previous equation) 7(8-2q)+12q=52 (multiply the first equation by 7) 56-14q+12q=52 (subtract 14q from 12q) 56-2q=52 (subtract the 56 from 52) -2q=-4 (multiply by -1) 2q=4 (divide by 2) q=2 p=8-2q (substitute the value of q) p=8-2(2) (multiply) p=8-4 (subtract) p=4 2p+4q=16 (check your answers with the new values of p and q) 2(4)+4(2)=16 8+8=16 true 7p+12q=52 7(4)+12(2)=52 28+24=52 true
Oh, dude, it's like this: if you have p plus q, you just add the two together. And then, if you have 2p, you're basically doubling p. So, technically, the answer is p + q and 2p. Hope that clears things up for ya!
P! / q!(p-q)!
If B is between P and Q, then: P<B<Q